Isolation and identification of endophytic fungi from Catharanthus roseus and Scutallaria barbata - Giang, Tran Thi Huong; Quan, Nguyen Duc; Linh, Duong Anh; Lan, Nguyen Ngoc; Huy, Le Quang; Lien, Nguyen Thi Kim; Hoang, Nguyen Huy (Academia Journal of Biology, 2021)
Endophytic fungi, microfungi that internally infect living plant tissues, are reported to have the ability to synthesize many enzymes, plant growth hormones and pharmaceutically active compounds similar to those in their hosted plants. This has opened a potential path of using endophytic fungi as a bioreactor for mass production of bioactive compounds at a lower cost. Therefore, it is necessary to establish a robust procedure for the isolation and identification of potential fungal strains that are capable of producing desired biological compounds. In this study, we reported an effective procedure for surface sterilization of 3 types of tissue samples (root, shoot and leaf) of 2 herbaceous plants (Catharanthus roseus and Scutallaria barbata) using commercial bleach (5% NaOCl), isolation of endophytic fungi from the sterilized samples and identification of isolated fungal strains by ITS sequencing analysis. A total of 48 endophytic fungi were successfully isolated from plant samples collected from Dan Phuong (Ha Noi), Phu Dien (Ha Noi) and Hai Duong city (Hai Duong). Based on results of morphological observation and ITS sequencing analysis, 48 endophytic fungi were classified to one of the four species, including Clasdosporium colombiae, Cladosporium halotolerans, Corynespora cassiicola and Albifimbria terrestris. The potential of the isolated endophytic fungal species for the mass production of pharmacologically active compounds will be investigated in future studies.